Design of Asynchronous Motor Soft Starting and Saving Energy Control Based on PLC - Xing-ping LIU (Institute of Advanced Engineering and Science, 2014)
For Asynchronous motor starting current impact is large, efficiency of running at light load is low. An energy-saving controller was designed with the PLC (Programmable Controller) as the core. It could realize the soft start and the energy saving control of motor when motor light run. The experimental results showed that: the energy-saving controller had the characteristics of stable starting, flexible parameter adjustment, energy saving effect obviously when motor light run DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4540